1990
DOI: 10.1111/j.1365-3121.1990.tb00072.x
|View full text |Cite
|
Sign up to set email alerts
|

The gold area of Jales (northern Portugal)

Abstract: The hydrothermal gold quartz veins of Jales cut Hercynian granitic rocks, Pre‐Ordovician, Ordovician and Silurian schists. They occur along Hercynian NNE‐SSW, NE‐SW and WNW‐ESE faults and are probably related to the Jales granite. Some are over 2 km long and have a thickness of 0.02–2 m. The only exploited quartz veins are from Campo and Desvio which contain several ore‐shoots (25t Au exploited since 1933). The veins from Jales area also have good Au reserves. Quartz and arsenopyrite dominate in the gold quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The occurrences of very small amounts of cassiterite, wolframite and scheelite in a few of these veins suggest that they may be genetically linked to the W-Sn deposits, which are closest to granite (Couto et al, 1990). Fractionation of felsic magma may concentrate gold (Neiva and Neiva, 1990;Neiva, 1992).…”
Section: Mineralizing Environmentmentioning
confidence: 99%
“…The occurrences of very small amounts of cassiterite, wolframite and scheelite in a few of these veins suggest that they may be genetically linked to the W-Sn deposits, which are closest to granite (Couto et al, 1990). Fractionation of felsic magma may concentrate gold (Neiva and Neiva, 1990;Neiva, 1992).…”
Section: Mineralizing Environmentmentioning
confidence: 99%
“…A importância de Canudos é exaltada pelas incontáveis teses, dissertações, livros, abordagens na música, na fotografia, nos filmes. Essa importância é refletida por Neiva (2017), em sua obra "Canudos, uma nova batalha":…”
Section: Luiz Paulo Neivaunclassified
“…Some authors (e.g. Neiva and Neiva, 1990), suggested a genetic relation between hydrothermal-fluid activity and late-stage fractional crystallization of granites for the Portuguese gold deposits. In contrast, Noronha et al (2000) concluded that the gold ores in quartz veins appear to be the result of three successive periods of fluid circulation in response to high heat flow and the intrusions of the granites: Stage 1 corresponds to the deposition of a milky quartz after the emplacement of synorogenic peraluminous granites; Stage 2 is characterized by a clear quartz and some sulfides and minor gold overprinting the early milky quartz associated with a fluid flow related with orogenic uplift and tectonic reactivation; and Stage 3 is characterized by intense microfissuring of the earlier minerals, deposition of more sulfides (galena, chalcopyrite and bismuthinite) in addition to native bismuth and sulfosalts (Pb-Bi-Ag dominant).…”
Section: Introductionmentioning
confidence: 99%